2012
DOI: 10.1186/1471-2431-12-91
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of resistance training in combination with botulinum toxin-A on hand and arm use in children with cerebral palsy: a pre-post intervention study

Abstract: BackgroundThe aim of this pilot study was to examine the effects of additional resistance training after use of Botulinum Toxin-A (BoNT-A) on the upper limbs in children with cerebral palsy (CP).MethodsTen children with CP (9–17 years) with unilaterally affected upper limbs according to Manual Ability Classification System II were assigned to two intervention groups. One group received BoNT-A treatment (group B), the other BoNT-A plus eight weeks resistance training (group BT). Hand and arm use were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
35

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 40 publications
0
29
0
35
Order By: Relevance
“…However, decision points or guidelines for progression or adaptation of the intervention based on individual participants' response to therapy were described by a few studies (Charles, Wolf, Schneider, & Gordon, 2006;Elvrum, Braendvik, Saether, Lamvik, Vereijken, & Roeleveld, 2012;Gordon, Schneider, Chinnan, & Charles, 2007;Gordon, Hung, Brandao, Ferre, Kuo, Friel et al, 2011). One study of resistance training and Botulinum Toxin injections described the grading of the program: "Once the participants were able to perform three sets of ten repetitions in an exercise, intensity was build up progressively on an individualized basis by increasing the weights by 0.25 -0.5kg."…”
Section: Research Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decision points or guidelines for progression or adaptation of the intervention based on individual participants' response to therapy were described by a few studies (Charles, Wolf, Schneider, & Gordon, 2006;Elvrum, Braendvik, Saether, Lamvik, Vereijken, & Roeleveld, 2012;Gordon, Schneider, Chinnan, & Charles, 2007;Gordon, Hung, Brandao, Ferre, Kuo, Friel et al, 2011). One study of resistance training and Botulinum Toxin injections described the grading of the program: "Once the participants were able to perform three sets of ten repetitions in an exercise, intensity was build up progressively on an individualized basis by increasing the weights by 0.25 -0.5kg."…”
Section: Research Interventionsmentioning
confidence: 99%
“…One study of resistance training and Botulinum Toxin injections described the grading of the program: "Once the participants were able to perform three sets of ten repetitions in an exercise, intensity was build up progressively on an individualized basis by increasing the weights by 0.25 -0.5kg." (Elvrum et al, 2012). Thirty-nine (65%) of studies adequately reported the procedure (Item 4) for the research intervention, detailing the activities and/or processes used.…”
Section: Research Interventionsmentioning
confidence: 99%
“…Twelve studies were of very high methodologic quality, scoring $8 on the PEDro scale. 10 Fourteen studies were of poor methodologic quality, scoring ,6 on the PEDro scale (BoNT-A, [21][22][23] cCIMT, 6,25,26 mCIMT, 7,29,30,38,44 forced-use therapy, 48 and other UL interventions 50,54,56 ). Twenty-six studies (57%) did not report concealed allocation.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
“…Thirteen types of UL interventions and numbers of participants were identified: NDT (2 studies; n = 122), 12,13 intramuscular injections of BoNT-A and OT (11 studies; n = 322), [14][15][16][17][18][19][20][21][22][23][24] cCIMT (3 studies; n = 56), 6,[25][26][27][28] mCIMT (15 studies; n = 578), 7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] hybrid model (mCIMT and bimanual training; 2 studies; n = 68), 8,9 forced-use therapy (2 studies; n = 54), 48,49 HABIT (1 study; n = 20), 50 OT home programs (1 study; n = 35), 51 UL lycra splints (1 study; n = 16), 52 contextfocused therapy (1 study; n = 128), 53 mirror box therapy (1 study; n = 10), 54 acupuncture combined with OT (1 study; n = 75), …”
Section: Description Of Studiesmentioning
confidence: 99%
“…Children with cerebral palsy are weak (Mockford and Caulton 2010). Considering the denervation effect of BoNT-A, structured upper-limb resistance training following BoNT-A should be considered (Elvrum et al 2012). It is important to recognize that in children muscle strength can occur in the absence of muscle hypertrophy following resistance training programs (Stackhouse et al 2005).…”
Section: Impairment Level: Stretching and Splintingmentioning
confidence: 99%